1989
DOI: 10.1111/j.1600-0714.1989.tb01339.x
|View full text |Cite
|
Sign up to set email alerts
|

New malignancy grading is a better prognostic indicator than Broders' grading in oral squamous cell carcinomas

Abstract: The prognostic value of histopathologic grading of oral squamous cell carcinomas (SCC) has varied from not any to highly significant. We have retrospectively studied all (130) SCCs registered in Norway 1963-72 in the buccal and maxillary alveolar mucosa. From 68 of these cases biopsy specimens of acceptable quality were obtained. Broders' method of grading was compared with a modification of a recent malignancy grading system recommended by Anneroth et al. which was performed only within the histologically mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
252
3
60

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(320 citation statements)
references
References 6 publications
5
252
3
60
Order By: Relevance
“…Could these models be used to predict which low-stage patients are at risk for disease-progression? Tumor pattern of invasion at the tumor host interface is a consistent component of these models [11][12][13][14][15][16][17][18][19][20]. Other components have included lymphocytic host response, exophytic versus endophytic growth pattern, mitotic rate, degree of keratinization, and nuclear pleomorphism.…”
Section: Predictors Of Occult Metastases: Tumor Depth Of Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…Could these models be used to predict which low-stage patients are at risk for disease-progression? Tumor pattern of invasion at the tumor host interface is a consistent component of these models [11][12][13][14][15][16][17][18][19][20]. Other components have included lymphocytic host response, exophytic versus endophytic growth pattern, mitotic rate, degree of keratinization, and nuclear pleomorphism.…”
Section: Predictors Of Occult Metastases: Tumor Depth Of Invasionmentioning
confidence: 99%
“…This cumbersome system was modified into a four-variable four-tiered system by Bryne [12][13][14]16] Attempts at validating the Bryne model, and pattern of invasion as a single indicator, however, were not always successful. Problems with the validation studies included small sample size, heterogeneous tumor sites and primary treatment modalities, plus evaluation of different specimen types, as some studies evaluated only biopsies, others only resection specimens, and still others evaluated both biopsies and resection specimens.…”
Section: Predictors Of Occult Metastases: Tumor Depth Of Invasionmentioning
confidence: 99%
“…Based on the histological grading proposed by Bryne et al 8 , two observers identified the front of tumor invasion (light microscopy -Olympus CX-31) and at a 1000x magnification and analyzed the presence or absence of immunostaining in the cell membrane, cytoplasm, nucleus or a combination of these. Then, it was performed a semi-quantitative analysis of the ß-catenin protein expression according to the technique described by Lee et al 9 , adapted for this study.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…There are reports that this grading is only of merit when used to evaluate deeply invasive margin (13)(14)(15)(16).…”
mentioning
confidence: 99%